On What Makes Some Video Games Philosophical - Mattis Benny (Open Philosophy)
As is evident from the observations of Ian Bogost and Thomas J. Spiegel, video games can be philosophical qua video games: they can express philosophical insights not only through verbal rhetoric, but also through the “procedural rhetoric” of the interactive processes defined by their programmed rules. However, prior work has not adequately explored what it is about some video games which make them particularly philosophically valuable. After reviewing previous literature and some relevant examples of procedural rhetoric, this article looks to Plato’s Phaedrus for an account of what distinguishes true philosophy from mere un-philosophical sophistry. Ultimately, this article suggests that if expressive artifacts (including video games) are to be evaluated qua works of philosophy, then they should be evaluated with reference to their usefulness in a broader context of dialectical exchange, rather than evaluated solely as standalone products.